Fish biomass data during Alkor cruise AL598 - Listmann, Luisa (PANGAEA, 2024)
This data set comprises all fish biomass data collected during the RV ALKOR cruise AL598 conducted in July/August 2023 (27th of July to 6th of August) in the Western Baltic Sea by the University of Hamburg. The cruise was part of the 5-year MARSYS teaching cruise program of the University of Hamburg GFP20-1_047. The fish biomass data were collected directly on board. Fish biomass was taken after sorting through a complete fish haul into the single species and weighing them on a scale on board.
Keywords: Baltic Sea; Field measurements; fish; RV ALKOR; summer; Teaching cruise